2013
DOI: 10.1038/ncomms3370
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive multiscale framework for simulating optogenetics in the heart

Abstract: Optogenetics has emerged as an alternative method for electrical control of the heart, where illumination is used to elicit a bioelectric response in tissue modified to express photosensitive proteins (opsins). This technology promises to enable evocation of spatiotemporally precise responses in targeted cells or tissues, thus creating new possibilities for safe and effective therapeutic approaches to ameliorate cardiac function. Here, we present a comprehensive framework for multi-scale modelling of cardiac o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
158
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 113 publications
(159 citation statements)
references
References 59 publications
1
158
0
Order By: Relevance
“…(13,15,57). At the organ scale, we used a finite element approximation of the steady-state photon diffusion equation to model light attenuation due to scattering and energy absorption in the ventricular myocardium (13,57). The corresponding partial differential equation, which assumes isotropic absorption and homogenous scattering, is given by:…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…(13,15,57). At the organ scale, we used a finite element approximation of the steady-state photon diffusion equation to model light attenuation due to scattering and energy absorption in the ventricular myocardium (13,57). The corresponding partial differential equation, which assumes isotropic absorption and homogenous scattering, is given by:…”
Section: Methodsmentioning
confidence: 99%
“…Data within the first 100 ms (i.e., t = 4-4.1 seconds) were excluded from analysis to ensure that these values were not biased toward either fast upstrokes associated with the initial response to optogenetic stimulation (i.e., directly light-induced action potentials) or low preillumination resting potentials. (13,15,57). At the organ scale, we used a finite element approximation of the steady-state photon diffusion equation to model light attenuation due to scattering and energy absorption in the ventricular myocardium (13,57).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Larger penetration depths and improved signal qualities have been demonstrated in whole hearts 30,[32][33][34] and heart slices 27,[37][38][39][40] using near-infrared voltage-sensitive dyes; however, imaging depth still remains limited. Thus, optical recordings of important features of the conduction system, such as the PS lying close to the endocardial surface, 41 have remained unexplored in the intact heart due to the inadequacies of current imaging methods.…”
Section: Optical Mappingmentioning
confidence: 99%
“…85 Experimental data have been used to develop computational models incorporating accurate representations of opsin channel kinetics, 83,86 spatial distribution of photosensitive cells, and tissue illumination constraints to determine the optimal targets for optogenetic stimulation in the whole heart. 41,87 For example, it has been computationally demonstrated that the optogenetic targeting of the PS, found close to the endocardial surface, could be used to optically perform cell-specific sinus-like pacing with lower energies compared with ventricular targets. 41 Although in vivo optical actuation has been demonstrated using openchest procedures in mice, 81 current recording methods are limited to the epicardial surface and subsurface due to photon scattering and absorption, making specific mapping of the internal conduction system infeasible.…”
Section: Emerging Cardiac Optogeneticsmentioning
confidence: 99%